Detection of Lawsonia intracellularis in wild boar and fallow deer bred in one game enclosure in the Czech Republic - Dezorzová-Tomanová, Katarína; Smola, Jiří; Trčka, Ivo; Lamka, Jiří; Pavlík, Ivo (Journal of veterinary medicine. Series B, 2006)
The prevalence of Lawsonia intracellularis between wild boar (Sus scrofa) and fallow deer (Dama dama) bred in one game reserve was investigated using the nested PCR method. In the study, 88 clinically healthy wild boars of different age categories and two fallow deer bagged in the game reserve were examined. Lawsonia intracellularis was demonstrated in the mucous membrane of the intestine of eight (9.1%) wild boars and one fallow deer. Of the nine wild boar whose tissues of corresponding lymph nodes were examined in addition to the mucous membrane of the ileum, one tested positive for the microorganism. A relationship between the occurrence of L. intracellularis and age of wild boar was demonstrated. Because wild boar and fallow deer are bred together in one game reserve, the possibility of inter-species transfer of L. intracellularis should be borne in mind.
Keywords: Lawsonia (bakterie); Deer; vysoká zvěř; DNA bakterií; Sus scrofa; prevalence; Female; infekce bakteriemi čeledi Desulfovibrionaceae; financování organizované; věkové faktory; Financing, Organized; zvířata; Desulfovibrionaceae Infections; Lawsonia Bacteria; DNA, Bacterial; ženské pohlaví; Male; polymerázová řetězová reakce; Czech Republic; Polymerase Chain Reaction; Prevalence; Age Factors; Animals; Česká republika; mužské pohlaví